Organizational Forgetting and Service Innovation Performance: The Mediation Role of Absorptive Capacity: A Moderated Analysis - Angga Negoro, Dimas; Astuti, Puji; Yanuar Rahmat Syah, Tantri; Pawirosumarto, Suharno (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to explore the effect of organizational forgetting on service innovation performance with absorptive capacity as mediation and to investigate the moderation role of transformational leadership. According to the results of previous studies and empirical theories related to the learning process and organizational innovation, this study was designed to collect data by a purposive sampling method from 232 service managers in the national headquarter, provincial, and district level of Indonesian Red Cross. The findings of this study are first, the positive influence among organizational forgetting and service innovation performance. Second, there is the mediating role of absorptive capacity and the moderating role of transformational leadership. The managerial implication of research for organizations is to increase the part of leaders in encouraging and ensuring and accustoming organizational forgetting for a better change and increasing organizational competitive and sustainable advantage.